2022
DOI: 10.3390/ma15186399
|View full text |Cite
|
Sign up to set email alerts
|

Residual Stress Redistribution Analysis in the Repair Welding of AA6082-T6 Aluminum Alloy Joints: Experiment and Simulation

Abstract: Residual stress has a three-dimensional scale effect (length, depth, and width) in the process of repair welding, which has a detrimental impact on the service of the aluminum alloy welded structures in high-speed trains. This paper aims to systematically analyze the effects of the repair welding dimension on the residual stress redistribution and obtain the optimal repair welding principles. A combination of blind-hole drilling method and stress linearization in BS7910 was adopted to investigate residual stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The findings of previous studies on butt welds in stainless steel tubes indicate that the rewelding procedure has a notable impact on the distribution of axial residual stress in neighboring heat-affected zones [21]. A distinct inference can be drawn from these findings, which suggests that the alteration in transverse stress is more pronounced when compared to the welding of new components with less stringent constraints [22,23]. Moreover, previous studies have indicated a positive correlation between the length of the weld and the magnitude of the increase in transverse residual stress [24].…”
Section: Introductionmentioning
confidence: 95%
“…The findings of previous studies on butt welds in stainless steel tubes indicate that the rewelding procedure has a notable impact on the distribution of axial residual stress in neighboring heat-affected zones [21]. A distinct inference can be drawn from these findings, which suggests that the alteration in transverse stress is more pronounced when compared to the welding of new components with less stringent constraints [22,23]. Moreover, previous studies have indicated a positive correlation between the length of the weld and the magnitude of the increase in transverse residual stress [24].…”
Section: Introductionmentioning
confidence: 95%